If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(n=+3)-10(n-5)=27
We move all terms to the left:
9(n-(+3)-10(n-5))=0
We add all the numbers together, and all the variables
9(n-3-10(n-5))=0
| -8g+7=-33 | | .-6x+2=6x-70 | | 3/20=p/100 | | 12x-5=6x | | m+22=43 | | 6n-2=(n-3 | | 45=-5h | | 5b–11=2 | | -3(x-4)+5x=10 | | 2n-10=-4 | | -(10-x)=7 | | 6(4n+3)=-174 | | 17-61=25-3r | | 4/3x−5/6=52 | | -8x+6(x+8=38 | | 17a-33=1 | | 5-6(a+12)=7+a | | 14/x+6=7/4 | | 9+g=-17 | | 3k-2k=2k-5-4K | | 6+4x=-x+6 | | –11=24+–5v | | (1/3)-x=(-1/2) | | 3x+2=4x–93.5x–8= | | v-4.6=98 | | 91=7(m+5) | | 48000=1/2m•20^2 | | 1.4–0.04x=5.20 | | 3q−=8 | | 4x+3-2x=8+2x | | |3x-4|-3=11 | | 3q−1=8 |